2019
DOI: 10.1007/s13197-019-03849-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam parboiling and hot soaking treatments on milling yield, physical, physicochemical, bioactive and digestibility properties of buckwheat (Fagopyrum esculentum L.)

Abstract: Post-harvest hydrothermal processing of grains are targeted at improving milling performances and nutritional properties. In this study, the effects of two hydrothermal processes, namely steam parboiling and soaking in boiling water for different durations on properties of buckwheat (Fagopyrum esculentum L.) grown in the Indian Himalayan regions were assessed. Both treatments significantly improved milling yield. Changes in grain section morphology were evidenced under scanning electron microscope. Milder proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…The results of this current research were consistent with Roy et al. (2019) and Bualuang et al. (2012).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The results of this current research were consistent with Roy et al. (2019) and Bualuang et al. (2012).…”
Section: Resultssupporting
confidence: 93%
“…However, Sirisoontaralak et al (2015) reported that germination had no effect on L* of GBR, when compared with BR. The results of this current research were consistent with Roy et al (2019) and Bualuang et al (2012). Chungcharoen et al (2015) and Roy et al (2019) reported that gelatinization of starch altered the color from murky white to translucent white, resulting in lower L*.…”
Section: Color Propertysupporting
confidence: 89%
See 2 more Smart Citations
“…Groats, produced from roasted and dehulled grains, are the most popular products obtained from buckwheat in many European countries and Japan [ 15 ]. Unit operations used in processing may affect the bioaccessibility of minerals to varying extent, changing the content of elements, but also causing degradation or formation of absorption inhibitors or stimulants, and the chemical species or salt solubility of a specific element may vary depending on the physical parameters and duration of the process [ 16 ]. The use of different methods of buckwheat groats production, using for that purpose different buckwheat grains, causes the nutritional value of groats available on the market to be different.…”
Section: Introductionmentioning
confidence: 99%